2018
DOI: 10.7150/thno.23853
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided surgery using near-infrared Turn-ON fluorescent nanoprobes for precise detection of tumor margins

Abstract: Complete tumor removal during surgery has a great impact on patient survival. To that end, the surgeon should detect the tumor, remove it and validate that there are no residual cancer cells left behind. Residual cells at the incision margin of the tissue removed during surgery are associated with tumor recurrence and poor prognosis for the patient. In order to remove the tumor tissue completely with minimal collateral damage to healthy tissue, there is a need for diagnostic tools that will differentiate betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 75 publications
1
41
0
Order By: Relevance
“…2019, 31,1904329 HFR-eNPs 565-700 nm [128] 2018 NanoCy7.5 100k-PBA 800-900 nm [129] OTL38 793 nm [130] Turn-ON probes 670 nm [131] 2019 THQ-Rosol 710 nm [132] RVG&IRDye800-Gd2O3 TNs 806 nm [133] SWNT-CY7-IGF-1Ra 770 nm [134] www.advmat.de www.advancedsciencenews.com Adv. Mater.…”
Section: Surface-enhanced Raman Spectroscopymentioning
confidence: 99%
“…2019, 31,1904329 HFR-eNPs 565-700 nm [128] 2018 NanoCy7.5 100k-PBA 800-900 nm [129] OTL38 793 nm [130] Turn-ON probes 670 nm [131] 2019 THQ-Rosol 710 nm [132] RVG&IRDye800-Gd2O3 TNs 806 nm [133] SWNT-CY7-IGF-1Ra 770 nm [134] www.advmat.de www.advancedsciencenews.com Adv. Mater.…”
Section: Surface-enhanced Raman Spectroscopymentioning
confidence: 99%
“…Another type of intraoperative imaging is by using fluorescence, which offers the benefits of high contrast, sensitivity, low cost, and by using appropriate microscope, visualization of cells and tissue in vivo and in vitro [27]. Different fluorescent probes are available for this purpose, such as "always on" low molecular weight probes with folate-receptor targeted fluorophore; "smart" probes, which are activated at the tumor site and are intact elsewhere; and "turn on" probes.…”
Section: Fluorescent Magnetic Resonance Imagingmentioning
confidence: 99%
“…However, an advantage of the use of fluorescent probes for imaging is that they can be engineered to be activated through specific molecular pathways. This will lead to personalization of the imaging methodology according to the patient's specific biomarkers [27].…”
Section: Fluorescent Magnetic Resonance Imagingmentioning
confidence: 99%
“…Brain oncology has similar requirements and recent developments have shown that it is possible to develop fluorescent nanoprobes that only turn on in a specific molecular environment. 49 Adapting this technology to MRI detectable probes that are only detectable when an ischemic penumbra is present would be a major advance for stroke diagnostics. Time-based gating of such fluorescencebased imaging has the potential to increase contrast by > 100-fold.…”
Section: Nanoparticles In Stroke Imaging and Diagnosticsmentioning
confidence: 99%